(untitled) (Research, Society and Development, 2024)
COVID-19, caused by the SARS-CoV-2 virus, is a severe acute respiratory disease with high transmissibility. The pandemic originated in China in 2019 and resulted in symptoms ranging from mild to severe, particularly affecting individuals with comorbidities. The virus utilizes the "spike" protein to enter human cells, initiating a replication process that can lead to widespread infection in the body. The pandemic reached Brazil in 2020, prompting various governmental actions. With increasing cases, searches for treatments, including the use of azithromycin, became common. Azithromycin, an antibiotic, had its efficacy in COVID-19 debated, especially when combined with hydroxychloroquine. Divergent studies emphasized the need for caution due to potential adverse effects and bacterial resistance. This study aims to report and critically evaluate the effectiveness and safety of azithromycin in treating COVID-19, providing evidence-based guidance.